Society Empowerment Using Assistance 6 in Tasikmadu with Bakso Ikan - Budi Prabowo; Didiek Tranggono; Praja Firdaus Nuryananda (Future Science)
This paper provides conceptual and practical descriptions for a model of empowering women fishermen based on local potential. The model is called the six-model model. The six developments model is the result of two years of research with objects of coastal community research in Sidoarjo Regency and Trenggalek Regency. This model has three stages, namely look-think-act. With this stage, the implementation of empowerment then focuses on six aspects, namely natural resource development, human resource development, institutional development, program development, business development, and environmental development. This paper will explain the application of the six communit development model in the coastal community of Tasikmadu village, Trenggalek Regency, as well as updating the previous research by utilizing the commodity of Bakso Ikan. Empowerment activities through the six development model in Tasikmadu Village were carried out by providing counseling and training on fish meatball production. After that, it was continued with the provision of a piece of fishball molding equipment to the Joint Business Group (KUB) Sumber Rejeki and Sumber Barokah in the hope that it would facilitate community economic turnover. With this series of activities, natural resource development, human resource development, and institutional development have been carried out. The business development, program development, and environmental development will still be the agenda of community service in the next assistance.